2012
DOI: 10.1007/s12020-012-9701-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concepts about prenatal genesis, aberrant metabolism and treatment paradigms in polycystic ovary syndrome

Abstract: The interactive nature of the 8th Annual Meeting of the Androgen Excess & PCOS Society Annual Meeting in Munich, Germany (AEPCOS 2010) and subsequent exchanges between speakers led to emerging concepts in PCOS regarding its genesis, metabolic dysfunction, and clinical treatment of inflammation, metabolic dysfunction, anovulation and hirsutism. Transition of care in congenital adrenal hyperplasia from pediatric to adult providers emerged as a potential model for care transition involving PCOS adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 112 publications
(114 reference statements)
1
11
0
1
Order By: Relevance
“…Androgen suppression reduces CRP and IL-6 in lean controls as early as 3 months after GnRH agonist administration. In contrast, we have shown that 5 days of oral androgen administration to elevate circulating androgens to levels comparable to PCOS induces a proinflammatory response in lean healthy reproductive-age women, [36,37]. This androgen treatment interval is too short to alter adiposity, and is consistent with the unaltered weight in lean controls of our current study in the face of the reduced inflammatory load following androgen suppression.…”
Section: Discussionsupporting
confidence: 82%
“…Androgen suppression reduces CRP and IL-6 in lean controls as early as 3 months after GnRH agonist administration. In contrast, we have shown that 5 days of oral androgen administration to elevate circulating androgens to levels comparable to PCOS induces a proinflammatory response in lean healthy reproductive-age women, [36,37]. This androgen treatment interval is too short to alter adiposity, and is consistent with the unaltered weight in lean controls of our current study in the face of the reduced inflammatory load following androgen suppression.…”
Section: Discussionsupporting
confidence: 82%
“…The severity of acne in adolescence is associated with several factors, including a positive history of severe acne in first‐grade relatives, especially the mother; occurrence in boys in early puberty; and occurrence in girls with notably elevated dehydroepiandrosterone sulfate serum levels during the adrenarche . Severe acne is in most cases a chronic disease, and is often a component of systemic diseases or syndromes …”
mentioning
confidence: 99%
“…Seborrhea, acne tarda and male-pattern baldness were very likely the results of the relative hyperandrogenism occurring in POI together with persisting amenorrhea, while the immunologic laboratory findings indicated the etiology of POI in our patient. Despite similar clinical signs, POI due to ovarian fibrosis is pathogenetically diverse from seborrhea-acne-hirsutism-androgenetic alopecia syndrome [8] and polycystic ovary syndrome [9], which are more familiar to dermatologists.…”
Section: Discussionmentioning
confidence: 99%